Effects of different light intensity on biosynthesis of medicine component (Phenolics and Flavonoids) and anti-oxidant activities in Malaysia young ginger varieties (Zingibber officinale Roscoe) under controlled environment - Ghasemzadeh, Ali; Jaafar, Hawa ZE; Rahmat, Asmah (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), UPM, 2010)
Plants secondary metabolites are considered to be able to modulate the human body’s biochemical and physiological processes, including its immunity systems. In light of this belief, research on medicine plants functional is widely conducted, including identification of bioactive compounds, evaluation on the interactions between plants compounds and specific functions in the body, and its immune modulation capability. Ginger (Zingiber officinale) is one of traditional folk medicinal plants and it is widely used in cooking in Malaysia. Four levels of greenhouse light intensities includes 310, 460, 630 and 790 umol m-2s-1 used in order consider effect of light intensities on production, accumulation and partitioning of total phenolics (TP), total flavonoids (TF) and antioxidant activities in tow varieties of Zingiber officinale. TF biosynthesis was highest in Halia Bara varieties under 310 μmol-2s-1 and TP was high in this variety under 790 μmol-2s-1 of light intensity. High content of these components accumulated in leaves and after that in rhizomes. Also antioxidant activities determined by the 1,1-Diphenyl-2-picryl-hydrazyl (DPPH) in both of varieties with increasing in TF concentration increased significantly (p<0.01) and high antioxidant activities observed in leaves of Halia Bara grown under 310 μmol-2s-1.